Firewood versus alternatives: domestic fuel in Mexico - Evans, M (Commenwealth Forestry Institute, University of Oxford, 1984)
A detailed survey of two contrasting villages in Mexico made in 1982 revealed a shortage not only of domestic firewood but also of liquid petroleum gas, the main alternative fuel. Quantitative evidence is given concerning the daily hardship this causes, particularly to women and children. Shortages were principally due to inadequate provisions for social forestry requirements on one hand and inadequate distribution systems of LPG in rural areas on the other. The village survey was subsequently placed in the context of the domestic fuel situation in central and southern Mexico...